Antioxidant Solution in Combination with Angiotensin-(1-7) Provides Myocardial Protection in Langendorff-Perfused Rat Hearts. (31st July 2020) - Andrä, Michaela; Russ, Miriam; Jauk, Susanne; Lamacie, Mariana; Lang, Ingrid; Arnold, Robert; Brcic, Iva; Santos, Robson; Wintersteiger, Reinhold; Ortner, Astrid
Abstract : As progressive organ shortage in cardiac transplantation demands extension of donor criteria, effort is needed to optimize graft survival. Reactive oxygen and nitrogen species, generated during organ procurement, transplantation, and reperfusion, contribute to acute and late graft dysfunction. The combined application of diverse substances acting via different molecular pathways appears to be a reasonable approach to face the complex mechanism of ischemia reperfusion injury. Thus, an antioxidant solution containing α -ketoglutaric acid, 5-hydroxymethylfurfural, N -acetyl-L-methionine, and N -acetyl-selenium-L-methionine was combined with endogenous angiotensin-(1-7). Its capacity of myocardial protection was investigated in isolated Langendorff-perfused rat hearts subjected to warm and cold ischemia. The physiological cardiac parameters were assessed throughout the experiments. Effects were evaluated via determination of the oxidative stress parameters malondialdehyde and carbonyl proteins as well as immunohistochemical and ultrastructural tissue analyses. It was shown that a combination of 20% (v / v ) antioxidant solution and 220 pM angiotensin-(1-7) led to the best results with a preservation of heart tissue against oxidative stress and morphological alteration. Additionally, immediate cardiac recovery (after warm ischemia) and normal physiological performance (after cold ischemia) were recorded. Overall, the results of this study indicate substantial cardioprotection of the novel combination with promising prospective for future clinical use.